Identities in Progress: Coming of Age in Contemporary Italian literature - Mendola, Martina (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of Italian, 2022)
This doctoral dissertation presents a comparative study of the challenges of growth portrayed in contemporary Italian literature, by looking at six coming-of-age stories published at the turn of the millennium. These novels are Mohsen Melliti's I bambini delle rose (1995), Simona Vinci's Dei bambini non si sa niente (1997), Niccolò Ammaniti's Io non ho paura (2001), Diego De Silva's Certi bambini (2001), Isabella Santacroce's Zoo (2006) and Tiziano Scarpa's Stabat Mater (2008). The study aims to unveil what it means to grow up in the early 21st century, and to generate a meditation on the status of the genre by understanding how the novel of formation is adapting to, or resisting an increasingly liquid society. In order to achieve these objectives, the methodology draws on theories from sociology of youth to philosophy, and from literary criticism to youth studies, to feed back into the analysis of the novels. In this way, the study uses interdisciplinarity to capture the vibrant dialogue that literature is able to establish with the social world.
APPROVED
Keywords: identity; italian literature; coming of age